The Contribution of Philosophy in Reconstructing Islamic Education - Tarigan, Mardinal (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
AbstractThe philosophy of Islamic education can be defined as a study of the various problems contained in the dynamics of education based on the Qur'an and al-Hadith as the main source and the opinions of experts as the second source. The philosophy of Islamic education becomes the concept of thinking about education based on Islamic teachings about the nature of human abilities to be fostered and developed and guided to become a Muslim man whose whole personality is imbued with Islamic teachings. By studying Islamic education philosophy means entering a fundamental, systematic, logical, and universal arena of thought derived from Islamic teachings.